DIGITALISASI PENDIDIKAN PADA SEKOLAH SWASTA BERBIAYA RENDAH DI MASA PANDEMI COVID-19 - Tajudin Tajudin; Yogi Sugiyana (Edulead : Journal of Education Management, 2021)
Digitization of education is an issue that is getting enough public attention today, as a response to drastically changing education services. Both the system in terms of learning, as well as the culture. The Covid-19 pandemic has forced students, teachers, and schools to experience digital technology-based educational activities. And the results can be predicted that almost all parties involved in the world of education complain of difficulties with this new emergency system. This difficulty is especially burdensome for schools which are financially and due to natural factors difficult to implement the digitalization of education. However, ready or not, the digitalization of education must be realized and accepted by all parties. This study aims to determine the effectiveness of the implementation of digitalization of education in low-cost private schools which of course from a financial point of view are greatly affected by the current pandemic conditions so that it becomes a formidable challenge for school leaders, where in addition to having to think about how to survive, schools can also finance their operations. must ensure distance learning can run more effectively and fun. This research uses a literature study approach and to obtain clear characteristics of the discourse in the form of theories and concepts studied, the authors use the content analysis method, to make inferences that can be replicated about what schools should prepare to welcome this new era of education regarding the application of digitalization of education so that in its application schools can provide a sense of security and comfort for students, teachers, and parents of students. Abstrak Digitalisasi pendidikan merupakan isu cukup mendapat perhatian publik saat ini, sebagai respon terhadap pelayanan pendidikan yang berubah secara drastis. Baik sistem dari sisi pembelajaran, maupun kulturnya. Pandemi Covid-19 telah memaksa siswa, guru, dan sekolah untuk merasakan aktivitas pendidikan yang berbasis teknologi digital. Dan hasilnya dapat diprediksi bahwa hampir semua pihak yang terlibat dalam dunia pendidikan mengeluh kesulitan dengan sistem baru yang sifatnya darurat ini. Kesulitan tersebut terutama sangat terasa membebani bagi sekolah-sekolah yang secara financial maupun karena faktor-faktor alamiah sulit untuk menerapkan digitalisasi pendidikan tersebut. Namun, siap atau tidak, digitalisasi pendidikan harus segera direalisasikan serta diterima oleh semua pihak. Penelitian ini bertujuan untuk mengetahui efektivitas penerapan digitalisasi pendidikan pada sekolah swasta berbiaya rendah yang tentunya dari sisi keuangan sangat terdampak dengan kondisi pandemic yang terjadi saat ini sehingga menjadi tantangan berat bagi para pemimpin sekolah, dimana selain harus memikirkan bagaimana agar sekolah bisa survive membiayai operasionalnya, juga wajib memastikan pembelajaran jarak jauh dapat berjalan lebih efektif dan menyenangkan. Kajian ini menggunakan pendekatan studi kepustakaan dan untuk mendapatkan karakteristik yang jelas dari wacana berupa teori dan konsep yang dikaji, penulis menggunakan metode content analysis, untuk membuat inferensi yang dapat direplikasi tentang apa yang harus disiapkan oleh sekolah untuk menyambut era baru dari dunia pendidikan ini terkait penerapan digitalisasi pendidikan sehingga dalam penerapannya sekolah dapat memberikan rasa aman dan nyaman bagi siswa, guru, dan orang tua siswa.